Conjugal transfer of a Sinorhizobium meliloti cryptic plasmid evaluated during a field release and in soil microcosms - Giusti, María de Los Ángeles (2013)
Horizontal gene transfer (HGT) is a central evolutionary mechanism that mediates the diversification and adaptation of bacteria in general and of rhizobia in particular. The few quantitative data on the conjugal transfer of rhizobial plasmids in soil correspond to the pSym (symbiotic genes-carrying replicons), with no information available regarding transfer frequencies in soil of other (namely accessory/cryptic) plasmids that are present in several rhizobial species. Thus, we examined here the conjugal transfer in non-sterile soil of the model Sinorhizobium meliloti cryptic plasmid pSmeLPU88b. Under field conditions the proportion of nodules containing indigenous rhizobia that acquired the plasmid pSmeLPU88b and then nodulated the trapping plants could be estimated as <0.1% (transconjugants/nodule) over an 18- month sampling period that followed inoculation. The collected evidence showed that the release of rhizobia by means of standard seed-inoculation procedures did not result in a massive transfer of the introduced cryptic plasmid pSmeLPU88b to the indigenous bacteria that nodulate trapping alfalfa plants. Using a laboratory microcosm system performed with the same soil from the experimental field, we demonstrated that transconjugants were generated in the rhizosphere at a frequency of ca. 1.43 106 transconjugants/recipient, a frequency from 102 to 103 times lower than that corresponding to the transfer of the same plasmid in rich-medium agar plates. The estimation of mobilization frequencies of rhizobial plasmids in soil is a necessary step toward the development of quantitative predictive models of gene-dispersal frequencies from inoculated strains to other rhizobia and soil bacteria.